2007
DOI: 10.1152/ajpgi.00233.2007
|View full text |Cite
|
Sign up to set email alerts
|

Transport of butyryl-l-carnitine, a potential prodrug, via the carnitine transporter OCTN2 and the amino acid transporter ATB0,+

Abstract: Srinivas SR, Prasad PD, Umapathy NS, Ganapathy V, Shekhawat PS. Transport of butyryl-L-carnitine, a potential prodrug, via the carnitine transporter OCTN2 and the amino acid transporter ATB 0,ϩ .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 63 publications
3
54
0
Order By: Relevance
“…141 Long-chain fatty acids are obligated to be processed this way, but SCFAs can also use this pathway too. 142 Thus, as Srinivas et al 135 reported, butyryl- l -carnitine can act as a prodrug for delivering butyrate into cells in vivo , and our own studies (article in preparation) found that butyryl- l -carnitines, PMX ™ 550B and PMX 550D (Fig. 6), are more potent HDACi than butyrate itself.…”
Section: Butyryl-l-carnitine Esterssupporting
confidence: 55%
See 1 more Smart Citation
“…141 Long-chain fatty acids are obligated to be processed this way, but SCFAs can also use this pathway too. 142 Thus, as Srinivas et al 135 reported, butyryl- l -carnitine can act as a prodrug for delivering butyrate into cells in vivo , and our own studies (article in preparation) found that butyryl- l -carnitines, PMX ™ 550B and PMX 550D (Fig. 6), are more potent HDACi than butyrate itself.…”
Section: Butyryl-l-carnitine Esterssupporting
confidence: 55%
“…Unlike the sugar transporters, which highly discriminate against synthetically modified sugars, the acylcarnitine transporters appear to tolerate a range of acyl-substrate variations 118 that can traverse both the plasma 118,135,140 and blood–brain barriers. 133,134 PMX 550B and PMX 550D are strong butyrate HDACi, and their potential for oral delivery and mitigation of short-half life may lead to more effective epigenetic therapeutics for treating the thalassemias, sickle-cell disease, neurological disorders, and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has poor pharmacokinetic properties (short half-life and first-pass hepatic clearance) and multigram doses are needed to achieve therapeutic concentrations in vivo Moos et al, 2016]. However, when butyrate and other SCFAs, including lipoic acid, present as acylcarnitine esters [Knoop, 1904;Bieber et al, 1982;Bieber, 1988;Nałezcz et al, 2004;Houten and Wanders, 2010], the body's natural carnitine-acylcarnitine transport machinery actively delivers the ester into cells, an effect that substantially increases the bioavailability of the corresponding acyl-CoA [Chenault et al, 1988;Billhardt et al, 1989;Srinivas et al, 2007;Gong et al, 2008;Piermatti et al, 2008;Rosca et al, 2009;Steliou et al, 2009Steliou et al, , 2012Parameshwaran et al, 2010Parameshwaran et al, , 2012.…”
Section: Apoptotic Priming In Mitochondriamentioning
confidence: 99%
“…Butyrate, a bacterial fermentation product, is beneficial for prevention/treatment of ulcerative colitis. 36 BC inhibited ATB (0, þ)-mediated Gly transport in mammalian cells, and BC induced Na þ -dependent inward currents under voltage-clamp conditions. BC inhibited OCTN2-mediated carnitine uptake, and transport of BC via OCTN2 was electrogenic, as evidenced from BC-induced inward currents.…”
Section: Ketoprofenmentioning
confidence: 87%